2013
DOI: 10.1080/10410236.2013.771560
|View full text |Cite
|
Sign up to set email alerts
|

Using Cognitive and Affective Illustrations to Enhance Older Adults’ Website Satisfaction and Recall of Online Cancer-Related Information

Abstract: This study examined the effect of adding cognitive and affective illustrations to online health information (vs. text only) on older adults' website satisfaction and recall of cancer-related information. Results of an online experiment among younger and older adults showed that illustrations increased satisfaction with attractiveness of the website. Younger adults were significantly more satisfied with the comprehensibility of the website than older adults, whereas older adults were more satisfied with perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 36 publications
1
72
0
3
Order By: Relevance
“…Several studies have shown that combining text with visuals improved recall of information (e.g., Morrow, Hier, Menard, & Leirer, 1998), while other studies only found positive effects for younger but not for older adults (e.g., Morrell, Park, & Poon, 1990), or no effects for both younger and older adults at all (e.g., Bol et al, 2014). With respect to audiovisual information, several studies have shown that videos improved recall of information in both younger and older adults as compared to text (e.g., Bol, Van Weert, De Haes, Loos, & Smets, 2015), while other studies have not found any difference between text and video (e.g., Corston & Colman, 1997).…”
Section: Theories Of Cognitive Learning: Unimodal or Multimodal Informentioning
confidence: 99%
“…Several studies have shown that combining text with visuals improved recall of information (e.g., Morrow, Hier, Menard, & Leirer, 1998), while other studies only found positive effects for younger but not for older adults (e.g., Morrell, Park, & Poon, 1990), or no effects for both younger and older adults at all (e.g., Bol et al, 2014). With respect to audiovisual information, several studies have shown that videos improved recall of information in both younger and older adults as compared to text (e.g., Bol, Van Weert, De Haes, Loos, & Smets, 2015), while other studies have not found any difference between text and video (e.g., Corston & Colman, 1997).…”
Section: Theories Of Cognitive Learning: Unimodal or Multimodal Informentioning
confidence: 99%
“…We wanted to keep the information on the webpage as constant as possible to ensure that recall was a function of the agerelated factors introduced rather than a function of various message-related factors that would interfere with age-related factors. For instance, if this study would have aimed to determine the role of text complexity, length, or type, we would have had to create different types of information, which calls for different research designs, such as experiments (Bol et al, 2014;Van Weert et al, 2011).…”
Section: Limitationsmentioning
confidence: 99%
“…For instance, involving and emotionally satisfying messages are known to increase patients' motivation to put cognitive effort into the processing of online information (Bol et al, 2014;Petty & Cacioppo, 1986). It has been argued that information is more deeply processed, and thus better recalled, when people are involved with the information (Petty & Cacioppo, 1986), and when they are emotionally satisfied with the information (Bol et al, 2014). We thus expect that increased website involvement and satisfaction with the emotional support from the website are positively related to recall of online cancer information among older cancer patients.…”
mentioning
confidence: 99%
“…For instance, the less complex the language and the more concrete presentations of healthrelated information (e.g., by including adequate visual cues and illustrations), the better the information are better recalled, especially by older adults (Kessels, 2003;cf. van Weert et al, 2011;Bol et al, 2014). However, rather than focusing on the language or content of the health-related messages, we aimed at contributing to the understanding to the impact of affective responses to the messages.…”
Section: Recall Of Medical Communicationmentioning
confidence: 99%